Transmediation in investigative journalism of Ecuador: analysis, challenges and case study - Sanguña, Jefferon (2020)
This article presents the results of an investigation that sought to determine what transmedia elements are in Ecuadorian investigative journalism from a case study and, from there, design journalistic products for press, radio and television that, together,constitute a proposal for a single transmedia narration. To fulfill this objective, the methodological strategy was an analysis of the contents of the report “Tarjeta roja” of the Vision 360 program that addressed corruption in Ecuadorian football. In addition, 16 interviews were conducted for the research and transmedia journalistic products was obtained.